Innovations in care : New concepts, new actors, new policies - Esquivel, Valeria Renata (2017)
Sustainable Development Goal 5 »Achieve gender equality and empower all women and girls« includesthe mandate to »recognize and value unpaid care and domestic work«. Target 5.4 calls for »the provision ofpublic services, infrastructure and social protection policies.« Together they offer a point of entry to advocatefor care policies at the national level.»Innovations in Care« contributes to understanding how care policies are being implemented in the Global South Sub-Saharan Africa, Asia and the Pacific, and Latin America and the Caribbean and the elementsthat have the potential to make them transformative in the sense of changing the structural inequalities associated with current ways in which care is provided and received (or not received), as opposed to simply remedying its worst effects. Taking Target 5.4 as the point of entry, the report assesses care services, care-related infrastructure and social protection policies through a care lens. Following Sustainable Development Goal 8 »Promote sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all« it also applies the care lens to labour market policies.This report is based on the specialized literature and on Beijing+20 country and regional reports produced by nations at the request of UN regional economic and social commissions, an exceptional and up-to-date sourceof information. It also draws on research by the United Nations Research Institute for Social Development andothers on the processes of claims making for care provision, including at the global level, and explores how care policies are framed and implemented in differentcontexts, the agendas that support their implementationand the tensions in implementing them. In doing so, it provides policymakers, development practitioners, womens movements and other stakeholders with concrete examples of care policies that can be replicated and scaled up to realize the transformative potential of the care agendaInnovations in care : New concepts, new actors, new policies.